Synthesis and redox behavior of new ferrocene-π-extended-dithiafulvalenes: An approach for anticipated organic conductors - Sarhan, Abdelwareth A. O.; Mohammed, Omar F.; Izumi, Taeko (Beilstein Journal of Organic Chemistry, 2009)
A number of new ferrocene-π-extended-dithiafulvalenes were successfully synthesized as new electron donor compounds. The chemical structures and electrochemical behaviors of these compounds were investigated using several spectroscopic methods. The synthesis of these compounds was achieved using the modified Wittig–Horner cross-coupling reaction using n-BuLi/THF at temperature varies from −78 °C to 0 °C. These new classes of bis(1,3-dithiafulvalene)ferrocenes have the 1,3-dithiole ring system separated by ferrocene as conjugated spacer. The ferrocene-dithiafulvalenes derivatives 9 and 12 were prepared as side products during the synthesis of the targeted compounds as bis(1,3-dithiafulvalene)ferrocenes 8, 10 and 11 in variable yields. The redox properties of the compounds have been investigated by cyclic voltammetry at ambient temperature using tetra-n-butylammonium perchlorate (TBAP) as the supporting electrolyte compared to ferrocene and the derivative 9. In CH2Cl2 on a Pt working electrode and at ambient temperature, two oxidation waves associated with two reduction waves at scan rates 100 mV s−1 were observed for 9 and 12. In contrast the anodic peak potential of bis(1,3-dithiafulvalene)ferrocenes 8, 10 and 11 exhibited two and three oxidation waves associated with two reduction waves.
Keywords: cyclic voltammetry; charge-transfer (CT) complexes; diacylferrocenes; electrochemical properties; ferrocene-π-extended-dithiafulvalenes [bis(1,3-DTF)Fc’s]; organic conductors